The integration of contemporary art and ethnic culture: taking the creation of ethnic fiber art as an example / Liang Xian and Mohd Jamil Mat Isa - Xian, Liang; Mat Isa, Mohd Jamil (Universiti Teknologi MARA, Perak, 2023)
The purpose of this research is to analyse the development trend of ethnic culture from the perspective of contemporary art, focusing on the art form of the expression of contemporary ethnic fibre art on ethnic culture. Through the research methods of questionnaire survey and case analysis of works, it is found that ethnic culture can show its artistic charm through diversified fibre art forms. Contemporary ethnic fibre art will be the innovative carrier of the integration of contemporary art and ethnic culture. In the case analysis of works, it is found that contemporary art and ethnic culture can be integrated into contemporary art creation through traditional handicraft innovation, pattern recombination and deconstruction, colour reference, national spirit, and other aspects. Therefore, this research proves that the integration of ethnic culture and fibre art is full of contemporary artistic interest, which not only enhances the social influence of ethnic culture, but also helps to enrich the form and content of contemporary fibre art, which is of great significance to promote the development of traditional ethnic craft.